Digital Infrastructure on Teaching Effectiveness of Public-School Teachers - Derder, Absolon; Sudaria, Ronel; Paglinawan, James (American Journal of Education and Practice, 2023)
Purpose: In the dynamic landscape of education, the integration of digital infrastructure significantly shapes public-school teachers' effectiveness. This study aims to investigate the interplay between digital infrastructure and teaching effectiveness, focusing on four subvariables: Access to Digital Infrastructure, Digital Pedagogical Skills, Technical Support and Infrastructure Maintenance, and Perceived Impact on Teaching Effectiveness. Specifically conducted at Old Damulog National High School, the research explores the current state of digital infrastructure, assessing teachers' access to resources and platforms. It also analyzes educators' digital pedagogical skills and evaluates technical support and infrastructure maintenance. The study aims to provide insights for policymakers, administrators, and educators, guiding the development of strategies to optimize digital infrastructure and enhance overall teaching effectiveness in public schools. Methodology: The quantitative research design was used on this study. A Survey Questionnaire was administered to public school teachers of Old Damulog National High School. The survey will include items related to access to digital infrastructure, digital pedagogical skills, technical support, infrastructure maintenance, and perceived impact on teaching effectiveness. Likert scales and closed-ended questions were used for quantitative data analysis. Findings: The study on "Digital Infrastructure and Teaching Effectiveness of Public-School Teachers" uncovers a multifaceted dimension. Teachers show varying access to digital resources, indicating potential disparities. Positive trends emerge in developing digital pedagogical skills, yet perceptions of technical support and infrastructure maintenance are moderate. The study emphasizes the importance of a robust feedback mechanism for infrastructure improvement and the necessity for comprehensive backup plans. Despite a generally positive perception of digital infrastructure's impact on teaching effectiveness, identified areas for improvement focus on providing structured professional development opportunities. These findings highlight the intricate interplay of access, skills, and support, emphasizing the need for targeted interventions to optimize digital tools in public-school teaching practices. Implications to Theory, Practice and Policy: The study highlights the need to refine existing frameworks to address the complex dynamics of digital infrastructure in teaching effectiveness. Educators and administrators can utilize these insights for targeted professional development, ensuring teachers have the requisite skills for optimal use of digital tools. The study emphasizes the importance of vigorous technical support and infrastructure maintenance for seamless integration. From a policy perspective, it advocates for comprehensive policies addressing access disparities, laying the groundwork for equitable digital education. Top of Form Recommendations: Based on the findings of this study, several key recommendations emerge to enhance the digital infrastructure and teaching effectiveness of public school teachers. Firstly, there is a critical need for targeted professional development opportunities to strengthen teachers' digital pedagogical skills. Administrators and policymakers should invest in training programs that focus on collaborative efforts and awareness of accessibility considerations, as highlighted by the literature. Secondly, addressing challenges in technical support and infrastructure maintenance is imperative. Schools must provide opportunities for teachers to offer feedback and suggestions for improving digital infrastructure, and comprehensive backup plans should be established to mitigate the impact of failures. Furthermore, policymakers should prioritize developing and implementing comprehensive policies that ensure equitable access to digital resources, minimizing disparities among students. Encouraging collaboration and resource-sharing among teachers can be instrumental in creating a supportive and dynamic digital learning environment.